P-3 The potentials of regional bereavement alliances for promoting best practice in bereavement care. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Brocklehurst, Tania; Cooper, Jan
Abstract : The Hertfordshire and Bedfordshire Bereavement Alliance is a coalition of bereavement service providers working across the NHS, private and charitable sectors to promote best practice in bereavement support provision. The group are accountable to our local End of Life Care Network Specialist Palliative Clinical Care Group – (NSPCCG) and as a pilot, sitting as a regional group of the newly formed National Bereavement Alliance (NBA). It is envisaged that such regional groups could be nationally formalised, under the National Bereavement Alliance, enhancing community engagement in line with initiatives such as the Ambitions for End of Life Care (2015) and the Compassionate City Charter (2015). The Hertfordshire and Bedfordshire Bereavement Alliance have adopted the Bereavement Care Service Standards (2014) as a work plan framework focussing on the seven work streams; Planning: For the Alliance to actively consider the needs of the bereaved population in Hertfordshire and Bedfordshire. Awareness and access: For the Alliance to support services and bereaved individuals with clear information on resources and signposting through a mapping exercise and production of a local resources directory. Assessment: For the Alliance to continue to support the development of an assessment tool that can be used by services and bereaved individuals in support of best practice. Support and supervision: For the Alliance to encourage and promote access to regular support and supervision for staff and volunteers in bereavement service provider organisations. Education and training: For the Alliance to continue the rollout of its education packages to enable access to bereavement training and development for staff and volunteers working with bereaved individuals. Resources: For the Alliance to support bereavement services in accessing appropriate resources for providing bereavement care. Monitoring and evaluation: For the Alliance to review and monitor its performance and support its member organisations to do so, thereby encouraging developments in bereavement services.